Desenvolvimento de uma análise sistêmica de cenários prospectivos para o setor de pelotas de minério de ferro brasileiro - Eduardo Pessotti Rangel (2012)
The iron ore mining sector has undergone profound changes in its fundamentals as a result of combined factors: demand growth, high quality reserves exhaustion and the geo-economic context. These changes have increased the complexity of the companies planning processes, mainly influenced by uncertainty and thenonlinear relationships of the critical variables of the industry dynamics. The methodologyof systems thinking and scenario planning was shown as an innovative alternative to understand and define robust strategies for the Brazilian mining sector (iron ore) to deal with current market dynamics. From scenarios produced by the combination of the uncertainties on the movement of sustainability and economic growth, this study concluded that the iron ore mining industry of Brazil is well positioned to take advantage of market opportunities and the pelletizing process was confirmed as the main technological alternative of this industry in the current economic context.